Model Konseptual Kinerja Pegawai: Kajian Literatur tentang Flexible Working Space, Employee Engagement, dan Organizational Citizenship Behavior - Dadang Syahputra; Khuzaini; Zakky Zambrudi; Syahrial Shaddiq; Prasetyo Yuli Usaid (PT. Hasba Edukasi Mandiri, 2026)
This study aims to examine the determinants of employee performance through a literature review approach by integrating competence, work engagement, organizational commitment, and self-efficacy. This research employs a qualitative method using a literature review of 13 relevant journal articles selected based on their relevance to the research variables. Data were collected through documentation techniques and analyzed using descriptive qualitative analysis by comparing, classifying, and synthesizing findings from previous studies. The results indicate that competence, work engagement, organizational commitment, and self-efficacy are key factors influencing employee performance. Competence has a direct effect on performance and also contributes to the development of self-efficacy and work engagement. Work engagement consistently shows a positive impact on performance, while organizational commitment emerges as the most stable variable, acting both as a direct determinant and as a mediator. However, the influence of self-efficacy shows inconsistent results, as it may affect performance either directly or indirectly through mediating variables such as organizational commitment or organizational citizenship behavior. This study highlights the need for a more integrated model to better understand the complex relationships among these variables. The findings are expected to contribute theoretically to the development of employee performance models and provide practical implications for organizations in improving human resource performance.